2019
DOI: 10.1097/bpb.0000000000000572
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and radiographic comparison of single-sugar-tong splint to long-arm cast immobilization for pediatric forearm fractures

Abstract: The purpose of this study was to compare the efficacy of a single-sugar-tong splint (SSTS) to a long-arm cast (LAC) in maintaining reduction of pediatric forearm fractures, while avoiding secondary intervention. One hundred patients age 3–15 with a forearm fracture requiring a reduction and immobilization were evaluated (50 LAC and 50 SSTS). Medical records and radiographs were reviewed at injury, postreduction, and at 1, 2, and 4 weeks postinjury. Sagittal and coronal angular deformities were recorded. Any se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 10 publications
0
1
0
Order By: Relevance
“…Study by Lee et al, 4 showed that loss of reduction occurred in 16 cases in short arm double splint group (34%) and 10 cases in sugar-tong splint group (29.4%), which did not differ significantly between the groups (p-value= 0.169). Murphy et al, 17 concluded that at four weeks post-injury follow-up, there were no statistically significant differences between use of an SSTS or LAC when comparing post-immobilisation sagittal alignment (LAC 10.3±7. 20 In the previous study by Colaris et al, 19 the results in the LACalone group were excellent in 21%, good in 38%, fair in 26%, and poor in 15%.…”
Section: Discussionmentioning
confidence: 99%
“…Study by Lee et al, 4 showed that loss of reduction occurred in 16 cases in short arm double splint group (34%) and 10 cases in sugar-tong splint group (29.4%), which did not differ significantly between the groups (p-value= 0.169). Murphy et al, 17 concluded that at four weeks post-injury follow-up, there were no statistically significant differences between use of an SSTS or LAC when comparing post-immobilisation sagittal alignment (LAC 10.3±7. 20 In the previous study by Colaris et al, 19 the results in the LACalone group were excellent in 21%, good in 38%, fair in 26%, and poor in 15%.…”
Section: Discussionmentioning
confidence: 99%
“…Since the risk of alignment changes after the fourth week in this age group is very low, the fourth week was chosen as the endpoint for radiological measurements. [ 7 ] At the time of admission, immediately after the reduction, the first-week, second-week, and fourth-week controls were analyzed. The types of fractures were recorded.…”
Section: Methodsmentioning
confidence: 99%
“…[ 3 - 6 ] There are different immobilization methods to maintain reduction in the conservative treatment of forearm fractures, such as short arm casts (SACs), long arm casts (LACs), single sugar-tong splints (SSTS) or double sugar-tong splints (DSTS). [ 7 ] Although the traditional immobilization method for pediatric distal forearm fractures is LAC, SAC and sugar-tong splints (STS) have shown satisfactory results in recent years. [ 4 , 7 - 9 ]…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations